2015
DOI: 10.1186/s12864-015-1293-y
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide survey and expression analysis of F-box genes in chickpea

Abstract: BackgroundThe F-box genes constitute one of the largest gene families in plants involved in degradation of cellular proteins. F-box proteins can recognize a wide array of substrates and regulate many important biological processes such as embryogenesis, floral development, plant growth and development, biotic and abiotic stress, hormonal responses and senescence, among others. However, little is known about the F-box genes in the important legume crop, chickpea. The available draft genome sequence of chickpea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 68 publications
(124 reference statements)
2
60
0
Order By: Relevance
“…F-box proteins are involved in degradation of cellular proteins. F-box proteins can recognize a wide array of substrates and regulate many important biological processes such as embryogenesis, floral development, plant growth and development, biotic and abiotic stress, hormonal responses and senescence (Gupta et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…F-box proteins are involved in degradation of cellular proteins. F-box proteins can recognize a wide array of substrates and regulate many important biological processes such as embryogenesis, floral development, plant growth and development, biotic and abiotic stress, hormonal responses and senescence (Gupta et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…6). F-box domain recognizes a wide array of substrates and regulates many important biological processes by degrading cellular proteins in plants [37].…”
Section: Group-jmjd6mentioning
confidence: 99%
“…It was identified that model plants of Arabidopsis contain 694 F-box genes [23]. Important crops also contain F-box genes-for example, rice, maize, soybean, and chickpea contain 678, 509, 359, and 285 F-box genes, respectively [25][26][27][28]. The same applies to perennial fruit crops, such as apples and pears, which contain 517 and 226 F-box genes, respectively [24,29], as well as perennial woody plants, such as Populus trichocarpa Torr.…”
Section: Introductionmentioning
confidence: 99%
“…The number of F-box genes of woody plants and herbaceous annual plants (Arabidopsis thaliana (L.) Heynh., rice, maize, and soybean) has high variation [24][25][26][27]29,30]. Under abiotic stresses, the expression profiles showed that the F-box gene family members play a crucial role in stress responsive pathways [25,28,31]. A total of 972 F-box genes were found in Medicago (Medicago truncatula Gaertn.…”
Section: Introductionmentioning
confidence: 99%